Evaluation of nutritional intake and malnutrition in critically ill patients and its relationship with 28-day death - Mohsen Rezaeian; Shiva Monfared-Parizi; Zahra Mousavi Shirazifard; Ahmadreza Sayadi; Hassan Khodadadi; Maryam Ghaseminasab-Parizi (Scientific Reports)
Abstract Malnutrition and risk for malnutrition in critically ill patients are associated with adverse outcomes. However, the adequacy of nutrient intake and its impact on malnutrition have not been entirely determined in previous studies. Above all, this study investigates the relationship between some nutrient intake and malnutrition levels and 28-day death. The observational study was done on patients over 18 years of age in Rafsanjan Intensive Care Unit (ICU) from April 21 to October 24, 2022. Subjective global assessment (SGA), modified nutrition risk in critically Ill (mNUTRIC) Score, demographic details and intake of some nutrients were assessed. Data was analyzed with SPSS 22 software, and a p-value of 0.05 was a significant level for all analysis.118 patients were studied. Malnutrition and mNUTRIC score are linked to 28-day mortality in logistic regression analysis (OR: 3.63, 95%CI 1.48–8.91, p = 0.004 and OR: 12.69, 95%CI 4.42–36.43, p < 0.001, respectively). There was no significant difference between the intake of some nutrients and malnutrition/ risk for malnutrition. This study reveals no relevance between nutrient intake with malnutrition and risk for malnutrition. Moreover, in malnourished patients, some nutrient intake was unrelated to the 28-day death. It is suggested that future studies be done with a larger sample size.